Hubungan Motivasi Belajar dan Keaktifan dalam Kegiatan Ekstrakurikuler terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas X SMA Negeri 10 Padang - Rina Sartika; Agustina .; Irfani Basri (Bahasa, Sastra, dan Pembelajaran, 2015)
Abstract: The purpose of this study is to describe the following .First , describe the critical reading skills of eighth grade students of SMP Negeri 34 Padang . Second , describe the argument essay writing skills class students of SMP Negeri 34 Padang VIII . Third , to describe the relationship between critical reading and writing essays arguing eighth grade students of SMP Negeri 34 Padang . The data of this study are the results of tests conducted on 26 to 28 November 2013 . The first test a number of questions about the objective with 30 items , which according to the indicator . The second test which tests the performance of the argument essay writing test . The data have been collected and analyzed statistically using the product moment formula . The results of the data analysis and discussion of the research results , we can conclude the following three points . First , the critical reading skills of eighth grade students of SMP Negeri 34 Padang are in good qualifying ( 77.11 ). Second , the argument essay writing skills eighth grade students of SMP Negeri 34 Padang are in good qualifying ( 80.27 ) . Third , there is a significant correlation ( mean ) between students' critical reading skills and writing skills essay argument eighth grade students of SMP Negeri 34 Padang at the 95 % significance level with n - 1 degrees of freedom is obtained t_hitung t_tabel = 4.65 and 1.70 in the sense t_hitung t_tabel is greater than 4.65 > 1.70 .